Effect of four different cooking methods on the fat digestion characteristics of yellow-feathered chicken - Mingzhu Sun; Yaqi Cao; Hongxia Liu; Tianran Huang; Zongshuai Zhu; Yuan Gao; Ming Huang (Applied Food Research)
The aim of this study was to investigate the effects of four cooking methods (boiling, microwaving, air frying and roasting) on the fat characteristics of chicken. The results showed that cooking significantly exacerbated fat oxidation, with boiling showing significantly lower level of malondialdehyde (MDA) at 0.25 ug/g. Microwaving, air frying and roasting significantly increased the levels of saturated fatty acids (SFA), while boiling decreased the levels to 1137.24 µg/g. In terms of digestive characteristics, in the gastric digestive fluid, the roast group had the largest particles while the boil group had the smallest particles. In the intestinal digestive fluid, boiled and microwaved chicken exhibited significantly smaller particle sizes, which was consistent with the trends in lipid droplet size and number observed by laser confocal. Boiling and microwaving significantly increased digestibility, reaching 51.51% and 54.25%, respectively. In conclusion, boiling could slow fat oxidation and reduce particle size, and promote lipid digestion.